(untitled) - Koshy, Valsa (London, 2010)
This book draws on Valsa Koshy's extensive experience of supervising researchers at all levels, and includes examples of Action Research carried out by practitioners across a range of topics and age groups. Case studies include UK and international examples, allowing you to reflect on multiple perspectives of Action Research in education.
Nghiên cứu cải tiến giảng dạy Tiếng Anh
Keywords: Action research in education; Handbooks, manuals, etc